2017
DOI: 10.5194/bg-14-1039-2017
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance of a grazed savanna grassland ecosystem in South Africa

Abstract: Abstract. Tropical savannas and grasslands are estimated to contribute significantly to the total primary production of all terrestrial vegetation. Large parts of African savannas and grasslands are used for agriculture and cattle grazing, but the carbon flux data available from these areas are limited. This study explores carbon dioxide fluxes measured with the eddy covariance method for 3 years at a grazed savanna grassland in Welgegund, South Africa. The tree cover around the measurement site, grazed by cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…In this study, a marked inter-annual variation of NPP was observed in the savanna ecosystem ( Fig. 3) consistent with the findings from other savannas (Moore et al, 2018a;Räsänen et al, 2017) and biomes (Knapp and Smith, 2001;Yang et al, 2011a). These results suggest that carbon accumulation fluctuates with annual precipitation.…”
Section: Inter-annual Variation Of Nppsupporting
confidence: 91%
“…In this study, a marked inter-annual variation of NPP was observed in the savanna ecosystem ( Fig. 3) consistent with the findings from other savannas (Moore et al, 2018a;Räsänen et al, 2017) and biomes (Knapp and Smith, 2001;Yang et al, 2011a). These results suggest that carbon accumulation fluctuates with annual precipitation.…”
Section: Inter-annual Variation Of Nppsupporting
confidence: 91%
“…including the statistical measurement error (Emeas) inherent in EC measurements and the error caused by gap filling of missing data (Egap) was estimated as follows (Räsänen et al, 2017):…”
Section: Appendix B: Uncertainty Analysis Of Neementioning
confidence: 99%
“…, Flanagan and Adkinson , Bradford and Crowther , Skinner , Rasanen et al. ), which could provide an improved understanding of hay production efficiency under rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem C fluxes, expressed as NEP:GEP ratio, could be used to quantify temporal variations in CUE as a fieldor farm-scale ecophysiological parameter for studying the proportion of C absorbed from the atmosphere for C accrual and hay production between contrasting pastures (Bradford and Crowther 2013). Moreover, these hayed agroecosystems may differ in their magnitudes and dynamics of photosynthetic surface and nitrogen (N) content (Lemaire et al 2007, Alberti et al 2010, Flanagan and Adkinson 2011, Bradford and Crowther 2013, Skinner 2013, Rasanen et al 2017, which could provide an improved understanding of hay production efficiency under rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%